Manajemen Pendidikan dalam Keluarga Upaya Mewujudkan Keluarga Sakinah - Syaiful Bahri (Journal Of Administration and Educational Management (ALIGNMENT), 2018)
The objective of the research was to analyze the management of education in family as the way to create a tranquil family. The method used in this research was qualitative descriptive method. The finding was the religous education in family consist of (1) pre and post natal education, (2) breast-feeding and sensitive period education, (3) childhood education, (4) adolescence education, (5) mature education and family education. In conclusion, education was required to be a tranquil family, begun from pre-natal to mature education. Keywords: Management, Religious Education, Tranquil Family